Connected Perfect Domination in Bipolar fuzzy graphs - Al-Kohily, Hameed; Shubatah, Mahioub M. Q. (IJRDO -JOURNAL OF MATHEMATICS, 2021)
In this paper we introduced and studied the concepts of connected domination γc(G) and tribal connected domination γtc(G) in bipolar fuzzy graphs. We determine the connected perfect domination number for some standard fuzzy graphs with suitable examples. We investigated the relationship of γc(G) and γtc(G) with other known parameters of G. Some bounds and some interesting results for the parameters are obtained. Further, we also obtain Nordhaus - Gaddum type results of γc(G). finally, the tribal connected perfect domination numberγtcp(G) for several classes of biploar fuzzy graphs are given with suitable example and obtain bounds for the same.